2020
DOI: 10.1371/journal.pone.0230922
|View full text |Cite
|
Sign up to set email alerts
|

Practice of parenteral nutrition in hospitalized adult patients in Korea: A retrospective multicenter cross-sectional study

Abstract: There have been no studies on the characteristics of parenteral nutrition (PN) supply for adult inpatients in South Korea. The aim of this retrospective multicenter cross sectional study was to investigate the current practice and characteristics of PN support in hospitalized adult patients in South Korea for the first time. This study was conducted retrospectively for the adult patients who were hospitalized and received PN in nine hospitals on August 1st, 2017 to October 30 th , 2017. We evaluated the type o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Only 18 patients (5.3%) received PPN; one patient with chronic intestinal failure, eight with acute intestinal failure, and nine with non–intestinal failure indications 11 . By contrast a recent retrospective multicenter cross‐sectional study of PN practices within Korean hospitals reported 71.2% of the 1439 patients who received PN during the 3‐month study period received PPN 12 . Although neither study reports the rationale or circumstances under which PPN was used over CPN, taken together with the data presented from our facility, it seems reasonable to assume that the use of PPN appears to be governed by factors specific to the facility rather than patient group per se.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Only 18 patients (5.3%) received PPN; one patient with chronic intestinal failure, eight with acute intestinal failure, and nine with non–intestinal failure indications 11 . By contrast a recent retrospective multicenter cross‐sectional study of PN practices within Korean hospitals reported 71.2% of the 1439 patients who received PN during the 3‐month study period received PPN 12 . Although neither study reports the rationale or circumstances under which PPN was used over CPN, taken together with the data presented from our facility, it seems reasonable to assume that the use of PPN appears to be governed by factors specific to the facility rather than patient group per se.…”
Section: Discussionmentioning
confidence: 95%
“…Where studies do exist, they frequently do not reflect contemporary PN practices, such as the use of shelf‐stable bags, catheter care bundles or management by a multidisciplinary nutrition support team (NST) 6,10 . Moreover, recent studies that report using PPN suggest wide variation internationally in the practices associated with the selection of route for PN delivery 11,12 . Furthermore, international evidence‐based guidelines on the use of PN appear to assume the provision of CPN, and do not make recommendations around clinical circumstances where the use PPN may be preferred over CPN 3,4,13 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of PN varies depending on country, methodology and period studied. It ranged from 0.68 % to 0.82 % considering total hospital discharges (1,2), and from 7.9 % to 12 % considering only hospitalized patients at any given time (3,4). In intensive care units (ICU), a worldwide study reported that around 10 % of patients received exclusively PN during 2007-2013 (5).…”
Section: Introductionmentioning
confidence: 99%